Peran Sektor Pertanian dalam Mendukung Ketahanan Pangan Nasional: Tinjauan Literatur dalam Perspektif Perekonomian Indonesia - Adha Mahyundari; Rey Septanislaus Togatorop; Nazwa Aulia Putri; Lokot Muda Harahap; Jos Bram Tamba; Muhammad Rayhan Satria; Kelvin Klementin (Jurnal Ilmiah Wahana Pendidikan, 2026)
The agricultural sector plays a fundamental role in Indonesia's economy and food security, yet its full potential remains largely unrealized. This study aims to examine the contribution of the agricultural sector to the national economy, its role in sustaining food security, and the challenges it faces in the era of globalization. A narrative literature review methodology was employed, analyzing eleven Indonesian-language scientific articles sourced from Google Scholar and Sinta-accredited journals published between 2020 and 2025. The findings indicate that the agricultural sector contributes significantly through three primary channels: the economic channel, encompassing contributions to regional gross domestic product and employment absorption; the production channel, consisting of domestic food commodity supply; and the social channel, involving the maintenance of rural communities as the foundation of national food production. Nevertheless, these contributions are constrained by structural challenges including low productivity, irreversible agricultural land conversion, ecological degradation, weak institutional coordination, and vulnerability to global geopolitical shocks. This study concludes that strengthening national food security requires an integrative policy approach, encompassing increased agricultural investment, local food diversification, multi-stakeholder synergy, productive land protection, and the integration of sustainable agricultural principles. Genuine food security can only be achieved when dimensions of productivity, ecological sustainability, and social justice are unified within a coherent policy framework that prioritizes the welfare of smallholder farmers.